2008
DOI: 10.1292/jvms.70.455
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hypertension and Effects of Benazepril Hydrochloride in a Canine Remnant Kidney Model of Chronic Renal Failure

Abstract: ABSTRACT. In order to determine whether hypertension would develop in dogs with chronic renal failure, we performed 7/8 renal ablation in 6 healthy dogs and compared pre-and post-ablation blood pressures determined by telemetry. One month after the renal ablation, blood urea nitrogen and creatinine were significantly increased (p<0.05), creatinine clearance was decreased (p<0.05), and blood pressure was increased significantly (p<0.05). Simultaneously, plasma renin activity, angiotensin I and II, and aldostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
2
13
1
1
Order By: Relevance
“…Strengths of this animal model include the ability to induce progressive renal insufficiency with only transient increases in systolic arterial pressure. Systemic arterial hypertension was not manifest in this study and others [13,35,36] despite the considerable loss of functioning nephrons and renal mass [37]. Systolic arterial pressure was transiently increased in CKD dogs but stabilized near baseline levels by the end of the 5-week period.…”
Section: Discussionsupporting
confidence: 40%
“…Strengths of this animal model include the ability to induce progressive renal insufficiency with only transient increases in systolic arterial pressure. Systemic arterial hypertension was not manifest in this study and others [13,35,36] despite the considerable loss of functioning nephrons and renal mass [37]. Systolic arterial pressure was transiently increased in CKD dogs but stabilized near baseline levels by the end of the 5-week period.…”
Section: Discussionsupporting
confidence: 40%
“…These variations are consistent with our previous findings, and support earlier observations from Piccione et al (2005). The levels of SBP and DBP reported herein are similar to those from earlier experiments in dogs (Mishina & Watanabe, 2008;Miyazaki et al, 2002;Mochel et al, 2013).…”
Section: Systolic Blood Pressuresupporting
confidence: 93%
“…Similar to temocapril, benazepril is also an ACEI that causes long-lasting and preferential biliary excretion. Significant antihypertensive effects of benazepril in dogs with CKD involving systemic hypertension have already been demonstrated experimentally and clinically in previous reports [9,13]. Although the findings from the present case indicated that temocapril is an effective antihypertensive agent, its superiority to other ACEIs has not yet been demonstrated.…”
Section: Discussioncontrasting
confidence: 46%
“…In human medicine, the term hypertensive nephrosclerosis (HN) was used to describe the renal injury caused by essential hypertension [9]. Although human HN is usually diagnosed solely on clinical grounds, importance of the pathological analysis of renal biopsy results has been pointed out recently [10,11].…”
Section: Discussionmentioning
confidence: 99%